Co-N-doped MoO2 nanowires as efficient electrocatalysts for the oxygen reduction reaction and hydrogen evolution reaction. (November 2017) - Yang, Linjing; Yu, Jiayuan; Wei, Zhaoqian; Li, Guixiang; Cao, Lindie; Zhou, Weijia; Chen, Shaowei
Abstract: Oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) are traditionally carried out with noble metals (such as Pt) as catalysts, respectively. Herein, Co-N-doped MoO2 nanowires catalysts were synthesized by employing MoO2 nanowires as templates and conductive substrates. The effect of nanowire structure and non-metal/metal doping on ORR and HER performance were scientific discussed. The most active Co-N-MoO2 (Co-N-doped MoO2 ) exhibited high ORR catalytic activity (an onset potential of +0.87 V vs. RHE, n values of 3.56 and 3.68, excellent electrochemical stability) and outstanding HER performance with a low overpotential (69 mV vs. RHE), high electrochemical area and robust stability in 0.1 M KOH, which are associated with the defined nanowires structure, and homogeneous doping of Co/N into MoO2 with numerous active sites. Graphical abstract: Highlights: Using MoO2 nanowires as templates and conductive substrates synthesized Co−N−MoO2 . The deliberate doping with N and Co atoms exhibited high activities for ORR and HER. The 1D conductive substrate with co-doping is attractive for heterogeneous catalysis.